2021
DOI: 10.1515/gps-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cr(vi)-tolerant Staphylococcus simulans assisting chromate evacuation from tannery effluent

Abstract: Chromium(vi) contaminated sites have been targeted for studying highly chromate-resistant bacteria. From a total of 23 Cr(vi)-resistant bacteria isolated on Luria-Bertani agar medium supplemented with K2CrO4 (1,500 μg/mL), only one strain UT8 (Staphylococcus simulans) was able to tolerate high concentration of chromate, i.e., up to 200 mg/mL in agar medium from tannery effluent. In acetate minimal medium (AMM), it showed maximum tolerance of up to 2,500 μg/mL. Cr(vi) removal potential was 94.6% after 24 h (K2C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Additionally, Cr-specific peaks were detected in Bacillus vietnamensis, Bacillus lentus, Alcaligenes faecalis, Staphylococcus cohnii , and Staphylococcus saprophyticus treated with 3400 mg/L Cr 6+ (Selvakumar et al, 2021 ). Su et al ( 2021 ) and Kalsoom A. et al ( 2021 ) indicated that the presence of Cr peaks could be due to the complexation of Cr 3+ ions with molecules located on the cell surface or the presence of reduced Cr 3+ species precipitated on the outer surface of the strains. The peak observed by the scientists (Kalsoom A. et al, 2021 ) was in the biomass of Staphylococcus simulans treated with 1500 μg/mL Cr 6+ (0.19 wt.% Cr).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Cr-specific peaks were detected in Bacillus vietnamensis, Bacillus lentus, Alcaligenes faecalis, Staphylococcus cohnii , and Staphylococcus saprophyticus treated with 3400 mg/L Cr 6+ (Selvakumar et al, 2021 ). Su et al ( 2021 ) and Kalsoom A. et al ( 2021 ) indicated that the presence of Cr peaks could be due to the complexation of Cr 3+ ions with molecules located on the cell surface or the presence of reduced Cr 3+ species precipitated on the outer surface of the strains. The peak observed by the scientists (Kalsoom A. et al, 2021 ) was in the biomass of Staphylococcus simulans treated with 1500 μg/mL Cr 6+ (0.19 wt.% Cr).…”
Section: Discussionmentioning
confidence: 99%
“…Su et al ( 2021 ) and Kalsoom A. et al ( 2021 ) indicated that the presence of Cr peaks could be due to the complexation of Cr 3+ ions with molecules located on the cell surface or the presence of reduced Cr 3+ species precipitated on the outer surface of the strains. The peak observed by the scientists (Kalsoom A. et al, 2021 ) was in the biomass of Staphylococcus simulans treated with 1500 μg/mL Cr 6+ (0.19 wt.% Cr).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aguilar-Barajas et al ( 2008) have reported the ChrR gene from Pseudomonas aeruginosa which is responsible for chromate resistance. Kalsoom et al (2021) have also reported the presence of chromate resistance genes (ChrR) from Staphylococcus simulans against chromate toxicity. It was evident that in the present study, the identi ed potent strain GP01 has the chromate reductase gene (ChR), which helps in the reduction of the Cr (VI) and helps the bacteria to withstand the extreme toxic conditions.…”
Section: Analysis Of Chromate Reductase Genes In Serratia Sp Gp01mentioning
confidence: 99%
“…Chromium (Cr) has been extensively used in many industrial applications (such as wood preservation, leather tanning, and textile dyeing) and is known to be one of the main toxic heavy metals [2]. Inappropriate disposal of effluent from these industrial activities has led to increased Cr(VI) concentrations in the environment, which triggered an alarming situation from the environmental safety perspective [3]. Cr exists in the form of chromium metal, hexavalent chromium (Cr(VI)), and trivalent chromium (Cr(III)).…”
Section: Introductionmentioning
confidence: 99%